ASSOCIATION OF NONPATHOGENIC FUSARIUM OXYSPORUM SPECIES WITH CULTURED SHOOT APICES OF BANANA (MUSA ACUMINATA) CULTIVARS - ANITA KUMARI; HARSH KUMAR (The Bioscan, 2015)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp.cubense is the most devastating disease worldwide. Management of disease is difficult through use of chemicals and very few cultivars are resistant. Nonpathogenic strains of Fusarium oxysporum act as biocontrol agent for the wilt disease by antagonizing and competing with the pathogenic strains for nutrients and root colonization sites. Shoot apices cultures of four banana cultivars Alpan, Malbhog, Robusta and Kothia on MS basal medium supplemented with 4.5mgL-1BAP and 0.2mgL-1IAA resulted in adventitious shoot differentiations. Some cultures showed appearance of endophytic fungal mycelium from the explant surface. Macroscopic and microscopic characterization of the isolated fungus suggested it to be Fusarium oxysporum. The fungal isolates were tested for their pathogenicity in tissue cultured plants of Fusarium wilt susceptible banana cv. Malbhog through root dip method. The non appearance of disease symptoms established the nonpathogenic status of the isolated Fusarium oxysporum strain. The frequency of association of non pathogenic Fusarium oxysporum was more in susceptible cvs. Alpan (13.65%) and Malbhog (13.07%) compared to resistant cv. Kothia (4.59%). Thus, there were endophytic association of non pathogenic Fusarium oxysporum strains in banana cultivars, which might be the reason of absence of the disease in the area.